2016
DOI: 10.1155/2016/3469395
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Dyspnea in a 40-Year-Old Man Caused by Giant Mediastinal Thymolipoma

Abstract: Thymolipomas are rare tumors of the anterior mediastinum containing both thymic stroma and an abundance of fat. We present a 40-year-old man with no underlying disease who presented with cough and progressive dyspnea. Clinical evaluation revealed a giant mass of lipid density filling almost the entire left hemithorax with mediastinal shift. Total excision of the 40 × 33 × 8 cm mass weighing 4 kg was performed via a left thoracotomy and the histopathologic diagnosis of the mass was reported as thymolipoma. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Computed tomography and magnetic resonance imaging are usually diagnostic. 6,7 Histopathologically, thymolipomas are composed of mature fatty tissue admixed with thymic tissue including epithelial islands and aggregates of mature lymphocytes. 1 In addition to classic morphology of thymolipoma, there are rare histologic variants in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computed tomography and magnetic resonance imaging are usually diagnostic. 6,7 Histopathologically, thymolipomas are composed of mature fatty tissue admixed with thymic tissue including epithelial islands and aggregates of mature lymphocytes. 1 In addition to classic morphology of thymolipoma, there are rare histologic variants in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…5 Histologic differential diagnosis of thymolipoma includes mediastinal lipoma, mediastinal liposarcoma, thymic hyperplasia, teratoma, and regressed thymoma. 2,7,10 Differentiation between lipoma and thymolipoma can sometimes be difficult. Identification of epithelial thymic cells with thorough sectioning and immunohistochemical markers is helpful for differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Differential diagnosis includes thymic hyperplasia, lipoma and liposarcoma of the mediastinum. [2] Lipoma will lack thymic epithelial tissue and liposarcoma will show higher degree of atypia and lipoblasts. In thymic hyperplasia, adipose tissue is usually not seen.…”
Section: Fig 3: a -Scattered Thymic Tissue Interspersed With Varyingmentioning
confidence: 99%
“…Thymolipomas are rare, slow-growing, benign anterior mediastinal neoplasms composed of an admixture of mature adipocytes and nonneoplastic thymic tissue. [1] Any age group can be affected [2] and accounts for 2-9% of all thymic neoplasms. [3] It is mostly an incidental finding that is diagnosed during a workup for other medical problems.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, cases of thymolipoma with progressive huge dimensions; it has been reported that there were symptoms of dyspnea, chest pain, cough and respiratory infections [4,5]. In the differential diagnosis of anterior mediastinal lesions, the most effective method in radiological evaluation is contrast-enhanced CCT [6,7].…”
Section: Case Reportmentioning
confidence: 99%